Empirical Study: Brand Performance and Consumer Satisfaction as Determinants of Brand Switching - Setyati, Dewi Ayudya; Dirgantara, Ahmad (PT Global Digital Sains Tekno, 2024)
In the current era of globalization, where changes in technology and the flow of information are increasingly advanced and rapidly encouraging the emergence of competition in the business world, consumer needs are not limited to the main function that can be provided for a product (primary demand), but develop into secondary needs (secondary primary), namely the desire for a brand. The purpose of this research is to determine the influence of brand performance on brand switching on Gudang Garam (GG) cigarettes, to determine the influence of brand performance on the level of brand satisfaction on GG cigarettes and to determine the influence of the level of brand satisfaction on brand switching on GG cigarettes. The research variables are brand performance, brand satisfaction and brand switching and the variable measurement scale used in this research is an interval scale, while the variable measurement technique uses the semantic differential technique. The sample for this research was people who bought and consumed GG brand cigarettes in East Jakarta, totaling 110 respondents. Analysis technique using One Step Approach to SEM (Structural Equation Modeling). Based on the test results, the hypothesis which states that brand performance and the level of brand satisfaction has a negative influence on brand switching is proven to be significant, while the hypothesis which states that brand performance has a positive influence on brand switching is also proven to be significant.